Multistep N2 Breathing in the Metal−Organic Framework Co(1,4-benzenedipyrazolate) - Salles, Fabrice; Maurin, Guillaume; Serre, Christian; Llewellyn, Philip L.; Knöfel, Christina; Choi, Hye Jin; Filinchuk, Yaroslav; Oliviero, Laetitia; Vimont, Alexandre; Long, Jeffrey R.; Férey, Gérard (Journal of the American Chemical Society, 2010)
A variety of spectroscopic techniques combined with in situ pressure-controlled X-ray diffraction and molecular simulations have been utilized to characterize the five-step phase transition observed upon N2 adsorption within the high-surface area metal−organic framework Co(BDP) (BDP2− = 1,4-benzenedipyrozolate). The computationally assisted structure determinations reveal structural changes involving the orientation of the benzene rings relative to the pyrazolate rings, the dihedral angles for the pyrazolate rings bound at the metal centers, and a change in the metal coordination geometry from square planar to tetrahedral. Variable-temperature magnetic susceptibility measurements and in situ infrared and UV−vis−NIR spectroscopic measurements provide strong corroborating evidence for the observed changes in structure. In addition, the results from in situ microcalorimetry measurements show that an additional heat of 2 kJ/mol is required for each of the first four transitions, while 7 kJ/mol is necessary for the last step involving the transformation of CoII from square planar to tetrahedral. Based on the enthalpy, a weak N2 interaction with the open CoII coordination sites is proposed for the first four phases, which is supported by Monte Carlo simulations.